Porous Silicon-Based Direct Hydrogen Sulphide Fuel Cells - Dzhafarov, T. D.; Yuksel, S. Aydin (AMER SCIENTIFIC PUBLISHERS, 2011)
In this paper, the use of Au/porous silicon/Silicon Schottky type structure, as a direct hydrogen sulphide fuel cell is demonstrated. The porous silicon filled with hydrochlorid acid was developed as a proton conduction membrane. The Au/Porous Silicon/Silicon cells were fabricated by first creating the porous silicon layer in single-crystalline Si using the anodic etching under illumination and then deposition Au catalyst layer onto the porous silicon. Using 80 mM H2S solution as fuel the open circuit voltage of 0.4 V was obtained and maximum power density of 30 W/m(2) at room temperature was achieved. These results demonstrate that the Au/Porous Silicon/Silicon direct hydrogen sulphide fuel cell which uses H2S:dH(2)O solution as fuel and operates at room temperature can be considered as the most promising type of low cost fuel cell for small power-supply units.
Keywords: Porous Silicon; Fuel Cell; Hydrogen Sulphide; Gold Catalyst; HUMIDITY-VOLTAIC CHARACTERISTICS; Chemistry; Science & Technology - Other Topics; Materials Science; Physics